Remarks on Appearing and Appearance in Husserl - Hopkins, Burt C. (Bollettino Filosofico, 2018)
A strand in the contemporary engagement with Husserl’s phenomenology is united by the critical judgment that the appearing of the appearance paradoxically does not appear in that phenomenology. I argue that it does. My argument has three parts. The first argues that, contra Heidegger, the appearance in Husserl doesn’t involve the “self-showing” of anything. The second argues that the appearance in Husserl is a phenomenon doubly purified, from 1) its index of existence and 2) its empirical facticity. The third argues that the appearing of the appearance appears in manifolds of lived-experiences that in turn appear in the only foundation that – from beginning to end – Husserl sought to establish for a philosophical science: the reflectively accessed unities of sense (Sinn) given in these manifolds that alone are capable of manifesting phenomenological evidence.